2018
DOI: 10.1523/jneurosci.2173-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Organization in the Inferior Colliculus Revisited with Cell-Type-Dependent Monosynaptic Tracing

Abstract: The inferior colliculus (IC) is a critical integration center in the auditory pathway. However, because the inputs to the IC have typically been studied by the use of conventional anterograde and retrograde tracers, the neuronal organization and cell-type-specific connections in the IC are poorly understood. Here, we used monosynaptic rabies tracing and hybridization combined with excitatory and inhibitory Cre transgenic mouse lines of both sexes to characterize the brainwide and cell-type-specific inputs to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 70 publications
(38 reference statements)
5
69
1
Order By: Relevance
“…Furthermore, information conveyed by interconnecting LG and GLU cells is likely to be different since both cell types receive different combination of extrinsic inputs (Chen, Cheng, Ito, & Song, 2018) and LG cells receive inputs from GLU cells in different synaptic domains (Ito & Oliver, 2014). Based on studies on rodents, LG neurons integrate information from multiple brainstem nuclei, while GLU cells integrate inputs related to their synaptic domains (Chen et al., 2018; Ito & Oliver, 2014; Ito et al., 2015). Therefore, it is suggested that LG cells control the entire IC circuit according to global state of brainstem nuclei, while GLU cells control according to the state of specific pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, information conveyed by interconnecting LG and GLU cells is likely to be different since both cell types receive different combination of extrinsic inputs (Chen, Cheng, Ito, & Song, 2018) and LG cells receive inputs from GLU cells in different synaptic domains (Ito & Oliver, 2014). Based on studies on rodents, LG neurons integrate information from multiple brainstem nuclei, while GLU cells integrate inputs related to their synaptic domains (Chen et al., 2018; Ito & Oliver, 2014; Ito et al., 2015). Therefore, it is suggested that LG cells control the entire IC circuit according to global state of brainstem nuclei, while GLU cells control according to the state of specific pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that GLU cells in different IC domains receive different combinations of extrinsic inputs, whereas GABAergic cells always receive a similar combination of extrinsic inputs (Chen et al . ). It has also been reported that some characteristics of sound besides characteristic frequency are coded in spatially organized ways inside the ICC (Schreiner & Langner, ; Rees & Langner, ).…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, a cell‐type‐specific monosynaptic retrograde tracing study revealed that inputs to GLU cells are related to their synaptic domain, whereas those to GABAergic cells are unrelated to the location of cell bodies and thus always similar (Chen et al . ). These results suggest that differences in the dendritic arborization and organization of presynaptic inputs underlie the different patterns of clustering for sound information between GLU and GABAergic neurons.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations